2020
DOI: 10.1101/2020.07.15.20154112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 antibodies in an entirely PCR-sampled and quarantined community after a COVID-19 outbreak - the CoNAN study

Abstract: Background: Due to the substantial proportion of asymptomatic and mild courses many SARS-CoV-2 infections remain unreported. Therefore, assessment of seroprevalence may detect the real burden of disease. We aimed at determining and characterizing the rate of SARS-CoV-2 infections and the resulting immunity in a defined population. Methods: CoNAN is a population-based cohort study in the previously quarantined community Neustadt-am-Rennsteig, Germany six weeks after a SARS-CoV-2 outbreak with 49 cases identifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 31 publications
5
44
3
1
Order By: Relevance
“…Our results of 12% IgG-seropositive participants corrected for test performance and a proportion of 25% asymptomatic infections are in line with the results from the German high-prevalence towns Gangelt [10] and Neustadt am Rennsteig [11]. Seroepidemiological studies conducted in Germany [12] The increased odds of infection after travelling abroad and after participating in larger events are in line with the outbreak history in Kupferzell.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results of 12% IgG-seropositive participants corrected for test performance and a proportion of 25% asymptomatic infections are in line with the results from the German high-prevalence towns Gangelt [10] and Neustadt am Rennsteig [11]. Seroepidemiological studies conducted in Germany [12] The increased odds of infection after travelling abroad and after participating in larger events are in line with the outbreak history in Kupferzell.…”
Section: Discussionsupporting
confidence: 85%
“…Seroepidemiological studies conducted in Germany [12] The increased odds of infection after travelling abroad and after participating in larger events are in line with the outbreak history in Kupferzell. From our study and the three other German studies with available data, the underascertainment ratio has been smaller than 6 [11,13,14] and not 10 or higher as in a number of international locations [17]. The association of seropositivity with very good self-reported health, although not statistically significant, may be indicative of lower risk awareness and less protective behaviour.…”
Section: Discussioncontrasting
confidence: 43%
“…A total of 18 studies were contact-tracing studies (CTSs), 7,10,12,16-31 with 3 based in schools, [29][30][31] and 14 studies were population screening studies. 7, [32][33][34][35][36][37][38][39][40][41][42][43][44][45] Two were high quality, 33,35 22 were medium quality, 10,12,16,21,22,[24][25][26][27][29][30][31][32]34,36,38,[40][41][42][43][44][45] 7 were low quality, [17][18][19][20]23,28,39 and 1 was uncertain quality. 7,37…”
Section: Resultsmentioning
confidence: 99%
“…Data from prevalence studies for children and adolescents compared with adults are shown in Figure 4. 7, [32][33][34][35][36][38][39][40][41][42][43][44][45] We did not undertake a meta-analysis of population screening studies given the important differences in the populations, epidemic time points, and methodologies involved.…”
Section: Population Screening Studiesmentioning
confidence: 99%
“…16,17 The current seroprevalence estimates are lower than the two other German community-based serosurveys. 14,15 However, both these previous serosurveys were conducted in communities following super-spreading events, and are unlikely to reflect the state of other regions in Germany with relatively low COVID-19 burden. 14,15 Neutralizing antibodies were detected in only about one third of the participants who tested positive on a widely used immunoassay.…”
Section: Discussionmentioning
confidence: 99%